Food Security Challenges in a Post-Productivist Agricultural Development Model in Pakistan - Sohail, Safdar (Journal of Public Policy Practitioners, 2024)
The further liberalization of wheat in Pakistan is being advocated on the premise that the previous model-centred around the minimum support price procurement by the government, is inefficient. The efficiency in wheat market will better address the welfare needs of ordinary consumers, with additional support from Benazir Income Support program and utility stores. Pakistan is about to enter in a new phase of manufactured food inflation. This phenomenon could be better understood by examining the last five years of the wheat policy as an example of capitalist operation. This study examines the policies and practices of wheat market in Pakistan over the last five years and their implications on food security and social market economy of wheat. Instead of responding to the excesses of neoliberalism by strengthening social market economy of wheat, we are set to expose a majority of the household to the full force of market, endangering food security at a large scale. This capitalist operation however, could not be effectively confronted by bringing back the old inefficient system. The findings of the study conceptualise the relationship between rising food insecurity in Pakistan and the ongoing deepening of market-oriented reforms in the wheat market. The research community in Pakistan needs to imagine new ways to realize the objectives of a social economy, as farmers risk losing the value they create to speculators and other investors in the supply chain. In an environment of post-productionism and hyper-capitalism, the value produced by a weak economic actor is likely to fall prey to the moneyed and more powerful entities unless they operate within a well-functioning social market economy.